The vascular morphology of melanoma is related to Breslow index: An in vivo study with dynamic optical coherence tomography. Issue 11 (9th October 2018) - De Carvalho, Nathalie; Welzel, Julia; Schuh, Sandra; Themstrup, Lotte; Ulrich, Martina; Jemec, Gregor B. E.; Holmes, Jon; Kaleci, Shaniko; Chester, Johanna; Bigi, Laura; Ciardo, Silvana; Pellacani, Giovanni
Abstract: Background: Malignant melanoma is an aggressive skin cancer, which can lead to metastasis development. Vascularization enhancement is fundamental for tumor growth, worsening the prognosis. Dynamic optical coherence tomography (D‐OCT) enables the in vivo evaluation of vascular patterns in skin lesions. Objective: In vivo evaluation of the melanoma vessel morphology by means of D‐OCT and correlation with Breslow index. Methods: Retrospective analysis of histologically proven melanomas, evaluated by D‐OCT at three different depths (150, 300 and 500 μm), was performed. Vessels were classified according to morphology (dots, blobs, coiled, line, curved, serpiginous), distribution (regular, irregular) and the presence/type of branches. The data were correlated with Breslow thickness. Results: A total of 127 melanomas were evaluated. Dotted vessels were recorded at all depths, and their irregular distribution was associated with lesions thicker than 1.0 mm (from 75% to 91%), compared with thin ones (42%) at 150 μm ( P  = 0.031), and from 33% to 57% vs 18% at 300 μm ( P  = 0.021). Serpiginous and branching vessels with bulges were predominantly seen in melanomas thicker than 2 mm at 150 μm (from 14% to 27%, P  < 0.001) and 300 μm of depth (from 36% to 54%, P  < 0.001). Limitations: Background noise hampered vessel detection at 500 μm. No correlation with dermoscopy/histology. Conclusion: Vascular pattern evaluation at 150 and 300 μm provided data on tumor microvascular asset and its pattern of progression in accordance with Breslow thickness. Since vascular progression is theoretically linked with tumor aggressiveness, the study of vascular pattern related with melanoma metastatization capability is warranted.